SOME TAXONOMIC FEATURES OF TRIATOMA SPINOLAI PORTER (HEMIPTERA: TRIATOMINAE) (Acta Entomológica Chilena, 2022)
A morphological description of eggs, nymphs and adults of Tnatoma spinolai is offered in this paper. Adetailed morphological descriptions of T. spinolai help to differenciate different populations of thisspecies.
Keywords: Triatoma spinolai - Chagas disease - Morphology; Taxonomy - Distribution